Automated width measurements of Martian dust devil tracks - Statella, Thiago; Pina, Pedro; Silva, Erivaldo Antonio da [UNESP] (Elsevier B.V., 2016)
Studying dust devils is important to better understand Mars climate and resurfacing phenomena. This paper presents an automated approach to calculate the width of tracks in orbital images. The method is based on Mathematical Morphology and was applied to a set of 200 HiRISE and MOC images of five Mars quadrangles, which were Aeolis, Argyre, Noachis, Hellas and Eridania. Information obtained by our method was compared with results of manual analysis performed by other authors. In addition, we show that track widths do not follow a normal distribution. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Martian dust devil tracks; Mathematical Morphology; Aeolian process